Bacterial chemoautotrophic reoxidation in sub-Arctic sediments:A seasonal study in Kobbefjord, Greenland - Vasquez-Cardenas, Diana; Meire, Lorenz; Sørensen, Heidi L.; Glud, Ronnie N.; Meysman, Filip J.R.; Boschker, Henricus T.S. (Marine Ecology Progress Series, 2018)
Anoxic mineralization of organic matter releases dissolved inorganic carbon and produces reduced mineralization products. The reoxidation of these reduced compounds is essential for biogeochemical cycling in sediments and is mainly performed by chemoautotrophic microbes, which synthesize new organic carbon by dark CO 2 fixation. At present however, the biogeochemical importance of chemoautotrophy in high-latitude sediments is largely unknown. Here, we determine the seasonal variation in sedimentary chemoautotrophic production in Kobbefjord (SW Greenland). Intact sediment cores from the fjord were incubated, and dark CO 2 fixation was quantified by combining bacterial phospholipid-derived fatty acid analysis with 13 C stable isotope probing (PLFA-SIP). Our results reveal a distinct seasonal cycle in chemoautotrophic activity, which increases after the spring bloom and shows lowest activity in the late winter when the fjord is covered by sea ice. The depth distribution of chemoautotrophic activity also varied seasonally, likely due to seasonal variation in the bioturbation activity of sediment infauna. Although chemoautotrophy rates (0.4 ± 0.2 mmol C m −2 d −1 ) were in the low range for coastal sediments, they are comparable to those from intertidal sandflats and brackish tropical lagoons, and scale with the sulfide production through sulfate reduction in the fjord. Chemoautotrophic production in these fjord sediments thus appears to be mainly driven by sulfide oxidation and can re-fix 4% of the CO 2 produced by mineralization.